Unlocking Potential: How Psychological Empowerment Transforms Employee Performance through Engagement and Organizational Culture - Lusiana, Herlina; Firdaus, F; Amelia, Citra (SAFE-Network, 2025)
This study examines the relationships between employee engagement, organizational culture, psychological empowerment, and employee performance within PT Tanjung Selatan Makmur Jaya. Employing a quantitative research framework, data was collected through a structured questionnaire administered to 152 employees selected via purposive sampling. The analysis employed the PLS-SEM technique, facilitated by SmartPLS software, to investigate the relationships among the variables. The findings suggest that employee engagement and organizational culture have a significantly positive impact on employee performance. Furthermore, employee engagement has a positive influence on psychological empowerment, which acts as a mediator in the relationship between organizational culture and employee performance. Conversely, psychological empowerment does not mediate the relationship between employee engagement and performance. This research highlights the crucial roles of employee engagement, organizational culture, and psychological empowerment in enhancing employee performance. It also elucidates the interactions among these factors, offering valuable insights for organizations seeking to develop more effective human resource management strategies that enhance employee performance in contemporary settings.